Maximizing T c by tuning nematicity and magnetism in FeSe1−x S x superconductors - K. Matsuura (Nature Portfolio, 2017)
The overlap between different phases has hindered the understanding of how each phase affects superconductivity in FeSe. Here, Matsuura et al. achieve a complete separation of non-magnetic nematic and antiferromagnetic phases for FeSe1-x S x , observing a tetragonal phase in between with a strikingly enhanced T c.